On the Problem of Linear Widths of the Classes B_p,θ^r of Periodic Functions of Many Variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish order estimates for the linear widths of the classes B_p,θ^r of periodic functions of many variables in the space L_q for some relationships between the parameters p, q, and θ.